Allogeneic hematopoietic SCT in combination with tyrosine kinase inhibitor treatment compared with TKI treatment alone in CML blast crisis - Jiang, H; Xu, L-P; Liu, D-H; Liu, K-Y; Chen, S-S; Jiang, B; Jiang, Q; Chen, H; Chen, Y-H; Han, W; Zhang, X-H; Wang, Y; et al. (Bone marrow transplantation (Basingstoke), 2014)
CML treatment with tyrosine kinase inhibitors (TKIs) has improved many patients’ prognosis, but during the disease’s terminal phase, the blast crisis (CML-BC), has been disappointing. Allo-HSCT is another treatment, but survival rates are still disappointing. Currently, a combination of these two is suggested but with little evidence. This retrospective comparison reports on this combination and TKI alone for treatment of CML-BC. Of the 83 CML-BC patients, 45 received TKIs (imatinib; nilotinb or dasatinib after imatinib resistance; TKIs group) and 38 were treated with allo-HSCT after TKI (TKIs+allo-HSCT group). Treatment success was measured in terms of the hematologic, cytogenic and molecular responses, and subject outcome. Follow-up was 30–126 months or until death. Univariate and multivariate analyses determined EFS and OS predictors. Allo-HSCT significantly improved the 4-year OS (46.7 vs 9.7%, P <0.001) and EFS (47.1 vs 6.7%, P <0.001) compared to TKI treatment alone. Hemoglobin <100 g/L, non-return to chronic phase after TKI therapy and TKI treatment alone are independent adverse predictors of OS and EFS. Allo-HSCT with individualized intervention after TKI therapy is superior to TKI alone for CML-BC.